Value of diffusion-weighted magnetic resonance imaging (DWI) in differentiating orbital lymphoma from idiopathic orbital inflammatory pseudotumor - Mohamed Saied Abdelgawad; Walid Mohamed Ahmed Mohamed; Rasha Abdelhafiz Aly (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Diffusion-weighted MR imaging can provide physiological information complementing morphological findings from conventional MRI. It detects early tissue changes associated with changes in water content, such as changes in the permeability of cell membranes, cell swelling or cell lysis. Areas of diseased tissue are highlighted with increased signal intensity on diffusion-weighted MR imaging. A decrease in the ADC is expected with increased intracellular tissue caused by either cell swelling or increased cellular density. DWI can be performed without the need for the administration of exogenous contrast medium, so it may of use when contrast administration is contraindicated. It yields quantitative and qualitative information that reflects changes at the cellular level and indicates the integrity of cell membranes. The purpose of this study was mainly to assess the diagnostic value of DWI for the discrimination of orbital lymphoma from idiopathic orbital inflammatory pseudotumor. Results Of our 53 cases presented with proptosis or visual disturbances, 32 cases (60.4%) had found to be present with idiopathic orbital inflammatory pseudotumor and 21 cases (39.6%) had orbital lymphoma. On conventional MR imaging, ill-defined tumor margin and orbital preseptal space involvement had a significant association with orbital lymphoma, whereas intense post-contrast enhancement of lesion and radiologic evidence of sinusitis were associated with orbital inflammatory pseudotumor. The mean ADC value of orbital lymphoma was significantly lower than those of benign inflammatory pseudotumor, yielding 100% sensitivity, 99% specificity, and 90.5% accuracy for differentiating both entities. Conclusions Diffusion-weighted MR imaging (DWI) is valuable in discriminating orbital inflammatory pseudotumor from malignant orbital lymphoma that help patients to initial management.